Early devonian organic-walled phytoplankton from the Ponta Grossa Formation, Paraná Basin, Brazil - García Muro, Victoria Josefina (2022)
The depositional sequence of the Ponta Grossa Formation (Paraná Basin) corresponds to a wave-dominated shallow marine environment, represented by four coarsening-upwards cycles, limited by flooding surfaces. Previous studies on a well-preserved and diverse assemblage of miospores indicated a late Pragian to possibly middle Emsian age. The palynological analysis of the Jaciara section is completed herein with the analysis of the marine fraction, composed of highly abundant and diverse organic-walled phytoplankton, with over 150 species recognized so far (Repository: EDDy Lab/Palynology). The phytoplankton species, such as Bimerga paula, B. sp. aff. B. bensonii, B. nuda, Cordobesia oriental, C. uruguayensis, Palacanthus ledanoisii, Pyloferites escobaides and Winwaloeusia distracta, recorded in the lower part of the section, indicate a late Pragian age, in coincidence with the miospores age. The clorophyte taxa, mainly  represented by the genera Cymatiosphaera, Polyedryxium and Pterospermella, are remarkably abundant in this part of the section. Navifusa spp. and Pterospermella pernambucensis first appear in the middle part of the studied section, suggesting an Emsian age, as do the miospores. It is noteworthy the abundance and morphological variability exhibited by the genera Pyloferites and  Schizocystia through the section, including some new species. The diversity and  preservation quality of the phytoplankton tend to decrease towards the top of the section, probably related to a general shallowing trend. The presence of Bimerga, Cordobesia, Pyloferites, Schizocystia and Winwaloeusia, restricted to Gondwana, corroborate affinities with this paleocontinent. The marine palynomorphs also evidence paleogeobiographical relationships with other Devonian South American basins of Brazil, Argentina, Bolivia and Uruguay.